(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This qualitative study explores the school-based instructional leadership role of Heads of Department (HODs) in the implementation of different History syllabi. It seeks to establish the practices that History HODs carry out in order to improve the teaching and learning of the subject. HODs are subject specialists who are responsible for establishing and ensuring high standards of teaching and learning in their subjects. This study is a response to the claim that History HODs often fail to rise to expectations in ensuring effective curriculum implementation in the subject. Qualitative data was collected through the study of circulars and policy documents and by conducting structured, in-depth interviews with fifteen key informants sampled from selected schools in the Glen View/Mufakose district in Harare. The key finding from this study is that the HODs were the de facto instructional leaders during the implementation of the History syllabi and that their level of involvement determines the success and/or failure of History syllabi. The paper concludes by asserting that HODs play a critical role in the implementation of History syllabi, since they are at the chalk face and directly supervise the implementation of changes in the subject as illustrated at five secondary schools used in the study.